Cloning, expression, purification, crystallization and preliminary X‐ray crystallographic analysis of the TIR domain from the Brucella melitensis TIR‐domain‐containing protein TcpB. Issue 10 (8th October 2013) - Alaidarous, Mohammed; Ve, Thomas; Ullah, M. Obayed; Valkov, Eugene; Mansell, Ashley; Schembri, Mark A.; Sweet, Matthew J.; Kobe, Bostjan
<x xml:space="preserve">Abstract</x> In mammals, Toll‐like receptors (TLRs) recognize conserved microbial molecular signatures and induce an early innate immune response in the host. TLR signalling is mediated by interactions between the cytosolic TIR (Toll/interleukin‐1 receptor) domains of the receptor and the adaptor proteins. Increasingly, it is apparent that pathogens target this interaction via pathogen‐expressed TIR‐domain‐containing proteins to modulate immune responses. A TIR‐domain‐containing protein TcpB has been reported in the pathogenic bacterium Brucella melitensis. Studies have shown that TcpB interferes with the TLR2 and TLR4 signalling pathways to inhibit TLR‐mediated inflammatory responses. Such interference may involve TIR–TIR‐domain interactions between bacterial and mammalian proteins, but there is a lack of information about these interactions at the molecular level. In this study, the cloning, expression, purification, crystallization and preliminary X‐ray crystallographic analysis of the protein construct corresponding to the TIR domain of TcpB (residues 120–250) are reported. The crystals diffracted to 2.6 Å resolution, have the symmetry of the monoclinic space group P21 and are most likely to contain four molecules in the asymmetric unit. The structure should help in understanding the molecular basis of how TcpB affects the innate immunity of the host.